Thermal Diffusivity of Gold Nanoparticle Reduced by Polyvinyl Alcohol Using Dual Beam Thermal Lens Technique. (2015) - Thomas, Lincy; John, Jisha; Kumar, B. Rajesh; George, Nibu. A.; Kurian, Achamma
Abstract: Dual beam Thermal lens technique is employed the thermal diffusivity of gold nanoparticle is synthesized using polyvinyl alcohol as reducing agent. The photoluminescence spectra of all the samples are carried out. The weight ratio of gold chloride increases the fluorescence peak shift towards lower wavelength and its fluorescence intensity decreases. Also the thermal diffusivity of gold nanofluid increases as the weight ratio of gold chloride increases.